1996
DOI: 10.1080/15216549600201622
|View full text |Cite
|
Sign up to set email alerts
|

Guanidino compounds generate reactive oxygen species

Abstract: SUMMARYMethylguanidine, guanidinoacetic acid and guanidinosuccinic acid are endogenous substances in body tissues. Extremely high levels of these substances are known to be related to the pathogenesis of epilepsy and renal failure such as uremia. In this study it was demonstrated that methylguanidine, guanidinoacetic acid and guanidinosuccinic acid, and arginine generate hydroxyl radicals in aqueous solution. These findings suggest that a high level of guanidino compounds accumulating near or within cells such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
2

Year Published

1998
1998
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 19 publications
2
31
2
Order By: Relevance
“…GAA induces oxidative stress after experimental intrastriatal infusion (Zugno et al 2008), or excessive accumulation in pathological conditions (Mori et al 1996), while dietary GAA improves antioxidant status by elevating total antioxidant capacity and the activities of several antioxidant enzymes (Wang et al 2012). Contrasting results of the previous studies are accompanied with different levels of GAA achieved after GAA administration/accumulation.…”
Section: Antioxidant Capacity and Enzyme Activitycontrasting
confidence: 53%
“…GAA induces oxidative stress after experimental intrastriatal infusion (Zugno et al 2008), or excessive accumulation in pathological conditions (Mori et al 1996), while dietary GAA improves antioxidant status by elevating total antioxidant capacity and the activities of several antioxidant enzymes (Wang et al 2012). Contrasting results of the previous studies are accompanied with different levels of GAA achieved after GAA administration/accumulation.…”
Section: Antioxidant Capacity and Enzyme Activitycontrasting
confidence: 53%
“…This observation suggests that dietary GAA has oxidant-antioxidant capacity (Ostogic et al, 2015). It has been shown that high levels of GAA could stimulate the generation of reactive oxygen species in the body (Mori et al, 1996), decrease non-enzymatic antioxidant capacity, and increase lipid peroxidation in rats (Zugno et al, 2008). This is observed as a higher heterophils to lymphocytes ratio (H:L) in birds fed GAA at 2 g/kg than in those fed with lower levels of GAA supplementation.…”
Section: Discussionmentioning
confidence: 56%
“…An increase in oxidants has been found in patients with end-stage renal diseases on chronic hemodialysis (CHD) [1,2]. Several reports indicated that CHD patients have higher plasma concentrations of lipid peroxide [3][4][5] and oxidation protein products [6,7] with a decrease in plasma antioxidants [3,8,9].…”
Section: Introductionmentioning
confidence: 99%